Transcranial Magnetic Stimulation as an Adjunct to Cognitive Behavioral Therapy for Obsessive-Compulsive Disorder. - Jalaluddin Rumi, Junaid Rasool, Muhammad Imran Khan, Sundus Ali Khan, Sadia Imran Cheema, Syed Ahmed Mahmud, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This randomized controlled trial investigated whether augmenting cognitive behavioral therapy(CBT) for obsessive-compulsive disorder (OCD) with repetitive transcranial magnetic stimulation(rTMS) over the supplementary motor area (SMA) enhances symptom reduction and modulatesbrain network connectivity. Eighty adults with moderate to severe OCD were randomized toreceive 8 weeks of CBT plus real rTMS or CBT plus sham stimulation